The relationship between causes of stress and organizational commitment among supporting staffs at Majlis Perbandaran Temerloh / Asihza Juliana Agusp - Agusp, Asihza Juliana (Faculty of Business and Management, 2020)
This research tries to clarify the relationship between cause of stress and organizational commitment among supporting staffs at Majlis Perbandaran Temerloh (MPT) by establishing an integrated framework for organizational commitment. The first objective for this research is to determine whether causes of stress have any influence an organizational commitment. Next the second objective is to determine the relationship between causes of stress and organizational commitment at Majlis Perbandaran Temerloh (MPT). The sample of this study is supporting staff at Majlis Perbandaran Temerloh (MPT). The researcher found that under cause of stress have two causes that are work overloaded and low task control while in organizational commitment have two components that is affective and continuance commitment.